Bilinguals implicitly name objects in both their languages: an ERP study - Von Holzen, Katie; Mani, Nivedita (Frontiers in Psychology, 2014)
Upon being presented with a familiar name-known image, monolingual infants and adults implicitly generate the image's label (Meyer et al., 2007; Mani and Plunkett, 2010, 2011; Mani et al., 2012a). Although the cross-linguistic influences on overt bilingual production are well studied (for a summary see Colomé and Miozzo, 2010), evidence that bilinguals implicitly generate the label for familiar objects in both languages remains mixed. For example, bilinguals implicitly generate picture labels in both of their languages, but only when tested in L2 and not L1 (Wu and Thierry, 2011) or when immersed in their L2 (Spivey and Marian, 1999; Marian and Spivey, 2003a,b) but not when immersed in their L1 (Weber and Cutler, 2004). The current study tests whether bilinguals implicitly generate picture labels in both of their languages when tested in their L1 with a cross-modal ERP priming paradigm. The results extend previous findings by showing that not just do bilinguals implicitly generate the labels for visually fixated images in both of their languages when immersed in their L1, but also that these implicitly generated labels in one language can prime recognition of subsequently presented auditory targets across languages (i.e., L2–L1). The current study provides support for cascaded models of lexical access during speech production, as well as a new priming paradigm for the study of bilingual language processing.